Crossing Gender Studies With the Commons: A Bibliometric Analysis - Périvier, Hélène (International journal of the commons, 2024)
Gender studies and commons studies have gradually developed to achieve academic recognition. They share common features : both fields lead to a rethinking of the boundaries between private and public spheres, renewing the definitions of ownership, labor, management, and resource sharing. They also pay specific attention to North-South relations. The concepts of gender and the commons are rooted in academia and are subject to various appropriations, particularly for programmatic purposes advocating for gender, environmental, and social justice. Crossing these two perspectives produces a heterogeneous body of knowledge, analysis, and recommendations. The purpose of this paper is to report on the diversity of literature at the intersection of gender studies and commons studies. We conduct a detailed bibliometric analysis based on an original database, Genre&Com. We quantify the dynamics of publications and dissemination, and the practices in terms of co-authoring and multidisciplinary collaboration. We also document the types of resources associated with the commons. Additionally, we compare the specificity of this dual field to the broader literature on the commons. Finally, we propose a framework to map this literature and apply it to the Genre&Com database. The ultimate goal is to facilitate the understanding and appropriation of this dual field by different categories of actors, including academics and practitioners.